PERANCANGAN UI/UX PADA APLIKASI WISATA LOMBOK MENGGUNAKAN METODE USER CENTERED DESIGN - Anggardika, Lalu Anugerah Wira; Albar, Mohammad Ali; Afwani, Royana (JTIKA (Jurnal Teknik Informatika, Komputer dan Aplikasinya), 2024)
This study investigates the application of User-Centered Design (UCD) principles in the design UI/UX for the mobile tourism application, 'Wisata Lombok.' The research aims to demonstrate how UCD can significantly improve user interface (UI) and user experience (UX) in context-specific applications. The methodology employed a multi-phase approach, including user research, persona development, iterative design. Data was collected through interviews with local and tourists, online surveys with Lombok residents, and on-site observations. This information guided the creation of user personas and informed the application's feature set and design decisions. Key findings reveal that incorporating local cultural elements into the UI design enhanced user engagement. The implementation of features like maps and cultural event calendars. Usability testing was carried out using an online questionnaire using the UEQ method. The UEQ contains 26 questions which structured in the form of a semantic differential, where each word consists of two terms expressing opposite meanings. The form was distributed to 35 respondents. All of the 35 respondents, 16 identified as male and 19 as female. The age distribution indicates that 29 respondents are within the 18-35 years old range, while 6 respondents are within the 35-56 years old. The UEQ result shows that the perspicuity and efficiency scale has the highest values, 2.29 and 1.96, falling within the “Excellent” range, indicating that the respondents didn't find any difficulties in operating the user interface. The attractiveness, dependability, and novelty scale fall within the “above average” value, indicating that the user interface was based on respondent needs. The stimulation scale has the least value 0.44 which fall within “bad” value , which means that the respondents was bored cause the user interface only has a few features.